The chapels of Saint Casimir and the Immaculate Conception at the Vilnius Cathedral in the eyes of Discalced Carmelite nuns: An unrecognized source from 1638 - Czyż, Anna Sylwia (Saeculum Christianum. Pismo Historyczne, 2021)
The article recalls a source from 1638 which has hitherto not been referred to in the literature on the subject, i.e. the history of two chapels at the cathedral in Vilnius: the Chapel of St. Casimir founded by King Sigismund III, and the Chapel of the Immaculate Conception, furnished as a burial chapel by Bishop Eustachy Wołłowicz (lit. Eustachijus Valavičius). The said source is a diary written by a Carmelite nun during her journey from Lublin to Vilnius (14 November – 26 December 1638), which she made with three fellow nuns assigned to a new monastery founded by Stefan Pac (lit. Steponas Pacas) and his wife Anna Maria Ancilia née Rudomina-Dusiatska (lit. Ona Marija Ancilia Rudomina-Dusiackaitė). The diary was penned by Sister Mary Magdalene (Anna Żaboklicka) who described various aspects of their journey, as well as a visit to the Vilnius Cathedral organized by the Pac family. The nuns were particularly impressed by the Chapel of St. Casimir. Thanks to Sister Mary Magdalene’s detailed description of the chapel, it was possible to reconstruct the subjects of some paintings by Bartłomiej Strobel, and to interpret several facets of its appearance, including the feretory of St. Casimir. While the description of Bishop Eustachy Wołłowicz’s chapel is not as detailed, it should be stressed that by inviting the nuns there, the Pac family intended to emphasize their kinship with the ruler of Vilnius, who was highly esteemed by his contemporaries.